Seizure outcome after corpus callosotomy: Prasat Neurological Institute Experiences - Tanpun, Adisak; Sudachan, Panisssara; Srikijvilaikul, Teeradej (Thai Journal of Neurological Surgery, 2025)
Purpose: Corpus callosotomy is an effective surgical treatment for medically intractable generalized seizures, especially in patients presented with drop attack. The aim of this study is to report the seizure outcomes after corpus callosotomy in a tertiary care epilepsy center. Methods: We retrospectively reviewed the medical records of all patients underwent corpus callosotomy at Prasat Neurological Institute. Only patients with more than 2-year postoperative follow-up were included in the study. Seizure outcome of callosotomy was categorized and analyzed by seizure type, including drop attacks and other kinds of seizures were analyzed. Results: There were 17 patients in the study during January 2013 and April 2019. Total callosotomy was performed in 3 (17.6%) patients the drop attack seizure-free rate was 33%, and seizure reduction rate was 66.6%. However, partial section yielded a drop attack free rate of 14.3%; the seizure reduction rate was 85.7%. There was no relapse of drop attack in both procedures consisted of partial and total corpus callosotomy. Conclusions: The study demonstrated the corpus callosotomy which treated effectively for disabling generalized seizures, especially for drop attacks. Total corpus callosotomy was more effective than the partial section in reduce drop attack seizures. However, overall seizure reduction was not different, and no relapse of drop attacks in both procedures.